Detection of Bovine Leukemia Virus in Argentine, Bolivian, Paraguayan and Cuban Native Cattle Using a Quantitative Real-Time PCR Assay-BLV-CoCoMo-qPCR-2 - Giovambattista, Guillermo (2025)
Bovine leukemia virus (BLV), an oncogenic retrovirus of the genus Deltaretrovirus, causes enzootic bovine leukosis (EBL), the most prevalent neoplastic disease in cattle and a major source of economic loss. While BLV prevalence has been studied in commercial breeds, data on native Latin American cattle remain limited. This study assessed BLV infection and proviral load in 244 animals from six native breeds: Argentine Creole (CrAr), Patagonian Argentine Creole (CrArPat), Pampa Chaqueño Creole (CrPaCh), Bolivian Creole from Cochabamba (CrCoch), Saavedreño Creole (CrSaa), and Siboney (Sib), sampled across Argentina, Bolivia, Paraguay, and Cuba. BLV-CoCoMo-qPCR-2 assay detected BLV provirus in 76 animals (31.1%), with a mean load of 9923 copies per 105 cells (range: 1–79,740). Infection rates varied significantly by breed (9.8% in CrAr to 83.8% in CrPaCh) and country (15.6% in Argentina to 83.8% in Paraguay) (p = 9.999 × 10−5). Among positives, 57.9% exhibited low proviral load (≤1000 copies), and 13.2% showed moderate levels (1001–9999), suggesting potential resistance to EBL progression. This is the first comprehensive report of BLV proviral load in Creole cattle across Latin America, offering novel epidemiological insights and highlighting the importance of native breeds in BLV surveillance.